032 Cognitive deficits are associated with anosmia but not anxio-depressive symptoms in COVID-19. (23rd August 2021) - Cysique, Lucette A; Allen-Davidian, Yasmin; Darley, David R; Byrne, Anthony; Wilhelm, Kay; Dore, Greg; Matthews, Gail; Brew, Bruce J
Abstract : Objectives: To characterise cognitive performance and olfaction in recovered COVID-19 patients. Methods: Patients underwent cognitive, olfaction and mental health assessments 2 months after initial SARS-CoV-2 infection as part of the Sydney St. Vincent's Hospital ADAPT study, a prospective cohort study. Cognition was assessed with the Cogstate computerised battery and expressed as a demographically-corrected composite z-score and clinically classified as impaired/borderline/unimpaired. Anxio-depressive symptoms were assessed with the Depression in the Medical ill scale-10 (DMI-10), the Somatic and Psychological HEalth Report-34 (SPHERE) Psych sub-scale, and the Impact of Events Scale-Revised (IESR) and reduced into single Principal Component explaining 80% of the variance. Olfaction was assessed with the NIH Toolbox Odor Identification test and expressed as demographically-corrected T-scores, and impaired/unimpaired. Disease severity was classified as mild (40%), moderate (50%) or hospitalised (10%). Results: 132 patients (mean age=46±15; 40% women, median education=16 years, 10% Non-English-Speaking Background-NESB) were included. 17% had impaired cognition, 10% had borderline deficits, 25% has impaired olfaction. 25% had clinically elevated symptoms on the DMI-10, 13% on the IESR, and 35% on the SPHERE. Regression analyses showed that anxio-depression was not associated with cognitive performance (unadjusted p=.43; adjusted for sex & NESB p=.98) nor impaired/unimpaired status (unadjusted p=.50; adjusted for sex & NESB p=.78). Cognitively impaired patients were more likely to have impaired olfaction (p<.009). Results were independent of disease severity. Conclusions: Cognitive impairment is common and not related to psychological factors, may occur independent of disease severity and is associated with anosmia. These point to direct brain effects of COVID-19.